Degradable polymer hemostatic sponge and preparation method and application thereof

CN118105533BActive Publication Date: 2026-10-16SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311536231.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2026-10-16
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

但该方法所制备的海绵孔径均匀性较差,难以控制表层及心层的孔隙均匀性,并且由于内部孔隙过大导致海绵力学性能有所下降

Benefits of technology

[0025] Beneficial effects: 1. Dopamine-modified oxidized hyaluronic acid is obtained by Schiff base reaction between the amino group of dopamine and the aldehyde group of oxidized hyaluronic acid. By introducing the catechol group on dopamine, the hemostatic sponge is provided with antioxidant function, which can eliminate reactive oxygen species and promote wound repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118105533B_ABST
    Figure CN118105533B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a degradable polymer hemostatic sponge, and comprises the following steps: S1, preparing a adipic acid dihydrazide-terminated polyurethane emulsion and oxidized hyaluronic acid respectively; S2, dissolving the oxidized hyaluronic acid in deionized water, adding dopamine hydrochloride after removing dissolved oxygen in the deionized water by using nitrogen, and reacting for 12 hours under the protection of nitrogen and in the dark; after that, the reaction liquid is dialyzed in deionized water for three days, and finally, the dopamine-modified oxidized hyaluronic acid with antioxidant function, active oxygen scavenging function and wound repair promoting function is obtained by freeze-drying. The dopamine-modified oxidized hyaluronic acid is obtained by Schiff base reaction between the amino group of dopamine and the aldehyde group of oxidized hyaluronic acid, and the introduction of the catechol group on dopamine provides the hemostatic sponge with antioxidant function, active oxygen scavenging function and wound repair promoting function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the medical field, specifically to a biodegradable polymer hemostatic sponge, its preparation method, and its application. Background Technology

[0002] Incompressible bleeding frequently occurs on battlefields, in traffic accidents, and in operating rooms, and accounts for the vast majority of all traumatic injury deaths. Incompressible bleeding can occur not only in pre-hospital settings but also suddenly throughout the entire treatment process, thus posing a high risk of death.

[0003] Hemostatic sponges are commonly used hemostatic packing materials for nasal bleeding. The porous structure of sponges provides high surface area and porosity, giving them a high absorption capacity for blood, while also being low in density and lightweight. In controlling this type of incompressible bleeding, sponges primarily work by rapidly absorbing water from the blood at the wound site, thereby concentrating clotting factors and enhancing the intrinsic coagulation cascade to promote coagulation. Simultaneously, the sponge expands after absorbing body fluid, generating pressure at the wound site for compression hemostasis. Furthermore, the porous nature of sponges allows them to be compressed into small shapes and sizes, adapting to irregular natural cavities and providing support and protection for the surgical cavity for a certain period. Therefore, sponge-like materials have great potential in controlling incompressible bleeding.

[0004] Chinese invention patent (CN116077713A) discloses a rapid hemostatic polyurethane elastomer hemostatic sponge and its preparation method. This patent uses a multifunctional chain extender to prepare a polyurethane prepolymer, which is then formulated with gelatin and a spinning solvent to form a homogeneous spinning solution for electrospinning. Finally, the sponge is cross-linked to obtain a hemostatic sponge. This hemostatic sponge is a three-dimensional fibrous material with a large specific surface area, extremely high porosity and water absorption, promoting the aggregation of coagulation factors and accelerating the coagulation process. However, this method, due to the introduction of the multifunctional chain extender, requires strict control of the reaction progress of the polyurethane prepolymer, placing high demands on the reaction process; furthermore, because the hemostatic sponge network exhibits a three-dimensional cross-linked structure, its biodegradability is relatively poor.

[0005] Chinese utility model patent (CN214209030U) proposes a nasal hemostatic cotton with a gradient distribution of pore size. This nasal hemostatic cotton is foamed from a composite material of water-soluble polyurethane and polyethylene glycol, and the pore size gradually decreases from the core of the material to the surface. It possesses characteristics such as compressibility, good resilience, and biodegradability. However, the sponge prepared by this method has poor pore size uniformity, making it difficult to control the pore uniformity of the surface and core layers. Furthermore, the excessively large internal pores lead to a decrease in the mechanical properties of the sponge.

[0006] Chinese invention patent (CN105944138A) discloses the preparation of a biodegradable medical polyurethane-chitosan composite hemostatic cotton. The method involves uniformly mixing chitosan with a prepolymer with two-terminated isocyanate groups to obtain a polyurethane-chitosan composite material, which is then dissolved in an organic solvent and freeze-dried to obtain the polyurethane-chitosan composite hemostatic cotton. However, due to the use of a large amount of organic solvent, this product inevitably suffers from problems such as the difficulty in removing the solvent, thus affecting its biocompatibility. In addition, it lacks antioxidant function, resulting in relatively slow wound healing.

[0007] To address the aforementioned issues, the applicant proposes a biodegradable polymer hemostatic sponge, its preparation method, and its applications. Summary of the Invention

[0008] The purpose of this invention is to provide a biodegradable polymer hemostatic sponge, its preparation method, and its application, in order to solve the problems in the prior art.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a biodegradable polymer hemostatic sponge, comprising the following steps:

[0010] S1. Prepare adipic acid dihydrazide-terminated polyurethane emulsion and oxidized hyaluronic acid, respectively;

[0011] S2. Dissolve oxidized hyaluronic acid in deionized water, remove dissolved oxygen from the deionized water with nitrogen, add dopamine hydrochloride, react in the dark under a nitrogen atmosphere for 12 hours, dialyze the reaction solution in deionized water for three days, and finally freeze-dry to obtain dopamine-modified oxidized hyaluronic acid with antioxidant function, scavenging reactive oxygen species and promoting wound repair after introducing catechol groups.

[0012] S3. The polyurethane emulsion capped with adipic acid dihydrazide is used as component A; the oxidized hyaluronic acid solution and the dopamine-modified oxidized hyaluronic acid solution are prepared together as component B, and mixed in different proportions to form a precursor solution. Under high-speed mechanical stirring, liquid nitrogen is added to the precursor solution in small amounts several times. After sufficient cooling and mixing, it is loaded into a mold, freeze-dried after being placed in sub-zero conditions overnight, and polyurethane-dopamine-modified oxidized hyaluronic acid sponge is obtained.

[0013] Optionally, the polyurethane emulsion with adipate dihydrazide end-capped in S1 is prepared as follows: a macromolecular diol is dehydrated at 90-100℃ for 2 hours, followed by the addition of aliphatic diisocyanate and organic bismuth, and then prepolymerized at 78℃ for 2 hours. After adding 2,2-dimethylolpropionic acid, the chain extension reaction is carried out at 75℃ for 1 hour. After cooling, an appropriate amount of acetone is added to dissolve the polyurethane prepolymer, and then triethylamine is added and reacted for 30 minutes. An appropriate amount of adipate dihydrazide is dissolved in deionized water and emulsified with the above polyurethane solution by high-speed stirring for 1 hour. After dialyzing in deionized water for three days using a dialysis bag with a molecular weight cutoff of 3500, the solid content of the emulsion is adjusted to finally obtain the polyurethane emulsion with adipate dihydrazide end-capped.

[0014] Optionally, the macromolecular diol includes one or more of polycaprolactone, polyethylene glycol, polytetramethylene glycol, and polylactic-co-glycolic acid copolymer; wherein the weight-average molecular weight of polycaprolactone is 600-2000; the weight-average molecular weight of polyethylene glycol is 400-2000; the weight-average molecular weight of polytetramethylene glycol is 800-2000; and the weight-average molecular weight of polylactic-co-glycolic acid copolymer is 1000-3000.

[0015] Aliphatic diisocyanates include at least one of L-lysine diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and isophorone diisocyanate.

[0016] The molar ratio of the aliphatic diisocyanate to the macromolecular diol is 2.0:1 to 3.0:1; the amount of the capping agent is 1.0 to 2.0 times.

[0017] Optionally, the molar ratio of the aliphatic diisocyanate to the macromolecular diol is 2.7:1, and the amount of the capping agent is 1.5 times.

[0018] Optionally, the specific preparation method of oxidized hyaluronic acid in S1 is as follows: weigh hyaluronic acid and add it to deionized water, stir to dissolve it completely; add sodium periodate solution that has been dissolved in deionized water in advance to the hyaluronic acid solution, react at 25°C in the dark for 8 hours, finally add an appropriate amount of ethylene glycol to terminate the reaction, then dialyze the reaction solution for three days and freeze dry to obtain oxidized hyaluronic acid.

[0019] Optionally, in S3, component A is an amino-terminated polyurethane emulsion with a mass fraction of 10-30%.

[0020] Component B is an aqueous solution of catechol-modified oxidized hyaluronic acid with a mass fraction of 2-5%, wherein the ratio of component A to component B is 1:2-2:1; and the ratio of oxidized hyaluronic acid to dopamine-modified oxidized hyaluronic acid is 3:1-1:1.

[0021] The hydrogel should be allowed to stand for at least 5 minutes to gel.

[0022] Optionally, the ratio of component A to component B is 1.5:1; the ratio of oxidized hyaluronic acid (OHA) to dopamine-modified oxidized hyaluronic acid (D-OHA) is 3:1; and the hydrogel settling time is 5 to 15 minutes.

[0023] Optionally, the biodegradable polymer hemostatic sponge prepared according to the method is also available.

[0024] Optional, the application of biodegradable polymer hemostatic sponges in biological hemostasis.

[0025] Beneficial effects: 1. Dopamine-modified oxidized hyaluronic acid is obtained by Schiff base reaction between the amino group of dopamine and the aldehyde group of oxidized hyaluronic acid. By introducing the catechol group on dopamine, the hemostatic sponge is provided with antioxidant function, which can eliminate reactive oxygen species and promote wound repair.

[0026] 2. The preparation process of the hemostatic sponge involves rapidly cooling the precursor solution by adding small amounts of liquid nitrogen multiple times, while simultaneously stirring at high speed to obtain numerous microbubbles and ice crystals. The bubbles and ice crystals are then removed by freeze-drying to obtain a hemostatic sponge with a dense microporous structure, which is characterized by compressibility, rapid blood absorption, softness, and uniform texture. Attached Figure Description

[0027] Figure 1 This is a synthetic route diagram of the hydrazide-terminated aqueous polyurethane emulsion according to an embodiment of the present invention;

[0028] Figure 2 This is a synthetic route diagram of dopamine-modified oxidized hyaluronic acid according to an embodiment of the present invention;

[0029] Figure 3 These are scanning electron microscope images from embodiments of the present invention;

[0030] Figure 4 This is a wet compressive modulus diagram according to an embodiment of the present invention;

[0031] Figure 5 This is a hemolysis rate diagram according to an embodiment of the present invention;

[0032] Figure 6 This is a BCI index chart according to an embodiment of the present invention;

[0033] Figure 7 This is a graph showing the free radical scavenging and antioxidant capacity of 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) according to an embodiment of the present invention.

[0034] Figure 8 This is a graph showing the free radical scavenging and antioxidant capacity of 2,2'-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) in an embodiment of the present invention. Detailed Implementation

[0035] The preferred embodiments of the present invention are described below with reference to the accompanying drawings to make the technical content clearer and easier to understand. The present invention can be embodied in many different forms, and the scope of protection of the present invention is not limited to the embodiments mentioned herein.

[0036] This invention provides a method for preparing a biodegradable polymer hemostatic sponge, comprising the following steps:

[0037] S1. Prepare adipic acid dihydrazide-terminated polyurethane emulsion and oxidized hyaluronic acid, respectively;

[0038] S2. Dissolve oxidized hyaluronic acid in deionized water, remove dissolved oxygen from the deionized water with nitrogen, add dopamine hydrochloride, react in the dark under a nitrogen atmosphere for 12 hours, dialyze the reaction solution in deionized water for three days, and finally freeze-dry to obtain dopamine-modified oxidized hyaluronic acid with antioxidant function, scavenging reactive oxygen species and promoting wound repair after introducing catechol groups.

[0039] S3. The polyurethane emulsion capped with adipic acid dihydrazide is used as component A; the oxidized hyaluronic acid solution and the dopamine-modified oxidized hyaluronic acid solution are prepared together as component B, and mixed in different proportions to form a precursor solution. Under high-speed mechanical stirring, liquid nitrogen is added to the precursor solution in small amounts several times. After sufficient cooling and mixing, it is loaded into a mold, freeze-dried after being placed in sub-zero conditions overnight, and polyurethane-dopamine-modified oxidized hyaluronic acid sponge is obtained.

[0040] like Figure 1 As shown, the preparation of adipic acid dihydrazide-terminated polyurethane emulsion (PU-ADH) is as follows:

[0041] The macromolecular diol was dehydrated at 90-100℃ for 2 hours, followed by the addition of aliphatic diisocyanate and organic bismuth, and then prepolymerized at 78℃ for 2 hours. After adding 2,2-dimethylolpropionic acid (DMPA), the chain extension reaction was carried out at 75℃ for 1 hour. After cooling, an appropriate amount of acetone was added to dissolve the polyurethane prepolymer, and then triethylamine was added and reacted for 30 minutes. An appropriate amount of adipate dihydrazide (ADH) was dissolved in deionized water and emulsified with the above polyurethane solution by high-speed stirring for 1 hour. After dialyzing in deionized water for three days using a dialysis bag with a molecular weight cutoff of 3500, the solid content of the emulsion was adjusted, and finally, an ADH-terminated polyurethane emulsion was obtained.

[0042] The aforementioned macromolecular diols include one or more of polycaprolactone (PCL), polyethylene glycol (PEG), polytetramethylene glycol (PTMG), and polylactic-co-glycolic acid copolymer (PLGA). Specifically, the weight-average molecular weight of PCL is 600–2000; the weight-average molecular weight of PEG is 400–2000; the weight-average molecular weight of PTMG is 800–2000; and the weight-average molecular weight of PLGA is 1000–3000.

[0043] Aliphatic diisocyanates include at least one of L-lysine diisocyanate (LDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), and isophorone diisocyanate (IPDI).

[0044] The molar ratio of aliphatic diisocyanate to macromolecular diol is 2.0:1 to 3.0:1, with 2.7:1 being the optimal choice. The amount of capping agent used is 1.0 to 2.0 times, with 1.5 times being the best.

[0045] Table 1 Raw material ratio of hydrazide-terminated waterborne polyurethane emulsions

[0046]

[0047]

[0048] Preparation of oxidized hyaluronic acid (OHA):

[0049] Weigh 3.8 g of hyaluronic acid (HA) into deionized water and stir until fully dissolved. Add 1.068 g of sodium periodate solution, which has been dissolved in deionized water beforehand, to the HA solution and react at 25°C in the dark for 8 hours. Finally, add an appropriate amount of ethylene glycol to terminate the reaction. The reaction solution is then dialyzed for three days and freeze-dried to obtain oxidized hyaluronic acid. The weight-average molecular weight of the hyaluronic acid can range from 80,000 to 2,000,000.

[0050] like Figure 3 The preparation process of dopamine-modified oxidized hyaluronic acid (D-OHA) is shown below:

[0051] 2.0 g of OHA was dissolved in 200 ml of deionized water. After removing dissolved oxygen from the deionized water with nitrogen, 3.026 g of dopamine hydrochloride was added. The reaction was carried out in the dark under a nitrogen atmosphere for 12 hours. The reaction solution was dialyzed in deionized water for three days. Finally, dopamine-modified oxidized hyaluronic acid (D-OHA) was obtained by freeze drying.

[0052] Preparation of polyurethane-dopamine modified oxidized hyaluronic acid hydrogel:

[0053] A polyurethane emulsion capped with adipic acid dihydrazide was used as component A; oxidized hyaluronic acid solution and dopamine-modified oxidized hyaluronic acid solution were prepared together as component B, and mixed in different proportions to form a precursor solution. After standing, the precursor solution formed a hydrogel, which was then freeze-dried to obtain a polyurethane-dopamine-modified oxidized hyaluronic acid hydrogel (PU-OHA-D hydrogel). The hydrogel that does not contain D-OHA is called a polyurethane-oxidized hyaluronic acid hydrogel (PU-OHA hydrogel).

[0054] Preparation of polyurethane-dopamine modified oxidized hyaluronic acid sponge:

[0055] A polyurethane emulsion capped with adipic acid dihydrazide was used as component A; oxidized hyaluronic acid solution and dopamine-modified oxidized hyaluronic acid solution were prepared together as component B, and mixed in different proportions to form a precursor solution. Liquid nitrogen was added to the precursor solution in small amounts multiple times under high-speed mechanical stirring. After thorough cooling and mixing, the precursor solution formed a homogeneous paste filled with microbubbles, which was then poured into a mold, freeze-dried after being incubated overnight at sub-zero temperatures, and the resulting polyurethane-dopamine-modified oxidized hyaluronic acid sponge (PU-OHA-D sponge) was obtained. The sponge without D-OHA in the component is called polyurethane-oxidized hyaluronic acid sponge (PU-OHA sponge).

[0056] The specific formulations of the hydrogel and sponge are shown in Table 2. Component A is an amino-terminated polyurethane emulsion with a mass fraction of 10-30%; component B is a composite solution of oxidized hyaluronic acid solution and dopamine-modified oxidized hyaluronic acid solution with a mass fraction of 2-5%. The ratio of component A to component B can be 1:2 to 2:1, preferably 1.5:1. The ratio of OHA to D-OHA can be 3:1 to 1:1, with 3:1 being optimal. The hydrogel should be allowed to stand for at least 5 minutes to gel, preferably 5-15 minutes.

[0057] After optimization, the optimal ratio of component A:component B was 1.5:1, and the optimal ratio of OHA:D-OHA was 3:1. A precursor solution was prepared by mixing a 20% adipic acid dihydrazide-terminated polyurethane emulsion, a 5% (w / w) oxidized hyaluronic acid solution, and a 5% (w / w) dopamine-modified oxidized hyaluronic acid solution in a ratio of PU:OHA:D-OHA = 6:3:1. Hydrogels and sponges were prepared and lyophilized for later use. A D-OHA-free hydrogel and sponge (PU:OHA = 6:4) were prepared using the same method and lyophilized for later use.

[0058] Table 2. Formulation composition of hydrogels and sponges

[0059]

[0060] The prepared sponge was characterized by various methods, including infrared spectroscopy, proton nuclear magnetic resonance spectroscopy, ultraviolet spectroscopy, mechanical properties, scanning electron microscopy, water absorption rate, hemolysis, antioxidant properties, and degradation properties.

[0061] like Figure 3 The four samples shown were freeze-dried, quenched in liquid nitrogen, sputter-coated with gold, and their internal pore structure was observed using a scanning electron microscope. The two groups of hydrogels had similar structures, both possessing macroporous structures (approximately 300 μm), but their pore size distribution was uneven, and some areas had incomplete pore structures. In contrast, the two types of sponges exhibited significantly smaller pore structures (approximately 150 μm), with more uniform and denser pores. This is because the rapid cooling with liquid nitrogen and high-speed stirring resulted in a large number of air bubbles and small ice crystals filling the interior. After freeze-drying, the internal structure was preserved, resulting in smaller, denser, and more complete pores. The density and porosity of the hydrogels and sponges were calculated using weighing and alcohol immersion methods. Compared to the hydrogels, the sponges prepared by the new method showed a significantly increased porosity and a slight decrease in density. Furthermore, the sponges absorbed water rapidly, reaching saturation in the initial state.

[0062] like Figure 4 As shown in the 70% compressive strain test under wet conditions, the compressive moduli of PU-OHA hydrogel and PU-OHA-D hydrogel are approximately 45 kPa and 54 kPa, respectively, while the compressive moduli of the two sponges are similar, at approximately 15 kPa. The significant difference in compressive modulus between the hydrogel group and the sponge group is due to their internal porous structure. Because the pores of the sponge are smaller and denser, and its internal pore walls are thinner than those of the hydrogel group, it is more easily deformed under external force. This soft sponge can better adapt to the shape of the wound during hemostasis, reducing patient pain.

[0063] like Figure 5 The in vitro hemolysis analysis of the different materials shown is a common method for assessing the blood compatibility of materials. Four samples were used as the experimental group, phosphate-buffered saline (PBS) as the negative group, and polyethylene glycol octylphenyl ether (Triton X-100) as the positive group. Each sample was immersed in a blood cell suspension prepared in PBS and then placed in a shaker at 37°C and 100 rpm for 1 hour. Then, 100 μL of the supernatant was transferred to a 96-well plate. The OD value at 540 nm was measured using a microplate reader. The hemolysis rate was calculated using the following formula:

[0064]

[0065] The hemolysis rates of the four samples were extremely low, with PU-OHA hydrogel and sponge at approximately 1% and PU-OHA-D hydrogel and sponge at approximately 0%, close to the negative group (0%). This indicates that the hydrogel and sponge did not have a significant destructive effect on red blood cells and had good blood compatibility.

[0066] like Figure 6 The image shows the in vitro coagulation index (BCI), which reflects in vitro coagulation performance. Medical gauze was used as the control group, and anticoagulated whole blood without calcium chloride solution was used as the blank group. Hydrogel and cryogel samples were placed in 24-well plates, anticoagulated whole blood and calcium chloride solution were added, and the plates were incubated at 37°C for 5 minutes. Then, 2 mL of deionized water was added along the plate wall, and the plates were incubated at 37°C for 10 minutes to allow all uncoagulated blood cells to swell and rupture. The supernatant (200 μL) was collected, and the OD value at 540 nm was measured using a microplate reader. The BCI index was calculated according to the formula.

[0067]

[0068] The more red blood cells the material adsorbs, the fewer ruptured red blood cells are produced after adding deionized water, resulting in lower absorbance and BCI index. As shown in the figure, the four materials are significantly lower than the gauze group (95%). The four materials themselves do not differ significantly, and their BCI indices are all around 20%, indicating that the four materials perform very well in in vitro coagulation and have a clear advantage in bleeding control.

[0069] like Figure 7 , Figure 8 The image shows the evaluation of the free radical scavenging and antioxidant capacity of the sponge using the free radical scavenging methods of 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) and 2,2'-adiazonium bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). 0.1 g of polyurethane membrane, hydrogel, and sponge were weighed into centrifuge tubes, and 4 ml of prepared DPPH free radical solution was added. After reacting in the dark for 5 min, 30 min, and 60 min, the OD values ​​of the DPPH solutions of each sample and the DPPH solution without the added sample were measured using a microplate reader. The DPPH free radical scavenging rate was calculated using the following formula:

[0070]

[0071] The operation of ABTS radical scavenging is basically the same, with the OD value measured at 734 nm and the formula being the same.

[0072] The trends in DPPH and ABTS free radical scavenging rates were similar. At 5 min, both the PU-OHA-D hydrogel and sponge containing dopamine exhibited extremely rapid free radical scavenging rates. The PU-OHA-D sponge group, in particular, reached 88% (DPPH) and 99% (ABTS) at 5 min, respectively, and remained stable at 30 and 60 min, reaching the upper limit of free radical scavenging at 93% (DPPH) and 100% (ABTS), making it the most efficient of the four samples. The PU-OHA-D hydrogel group had a slightly lower scavenging rate than the PU-OHA-D sponge group, reaching 61% (DPPH) and 95% (ABTS) at 5 min, eventually reaching 89% (DPPH) and 100% (ABTS), making it the second most efficient of the four samples after the PU-OHA-D sponge group. The two groups of PU-OHA hydrogel and PU-OHA sponge without dopamine showed comparable performance, with clearance rates of approximately 63% (DPPH) and 45% (ABTS) after 60 minutes, respectively. This was significantly lower than the two groups containing dopamine, particularly evident in ABTS free radical scavenging. The high free radical scavenging efficiency of PU-OHA-D containing dopamine is attributed to the catechol structure on the dopamine component. Therefore, PU-OHA-D sponge possesses excellent antioxidant properties, effectively removing excess reactive oxygen species from the wound site and maintaining redox homeostasis to promote wound healing.

[0073] After lyophilizing the hydrogel and sponge samples, the original weight (W0) was measured. The samples were then immersed in 5 mL of PBS (pH = 7.4) and placed in a temperature-controlled rotary shaker at 37°C and 90 rpm. After 7, 14, 21, and 28 days, the immersed hydrogel and sponge were lyophilized and weighed to obtain the final weight (W0). f The remaining weight ratio is calculated using the following formula to obtain the in vitro degradation rate curve.

[0074]

[0075] Compared to PU films, both hydrogels and sponges exhibited significant degradation within the first 21 days, with approximately 80% of their original mass remaining, indicating that both hydrogels and sponges possess certain degradation properties. In summary, through the introduction of dopamine and a novel sponge preparation process, we have prepared a biodegradable hemostatic sponge with uniform micropores, compressibility, a soft and uniform texture, antioxidant properties, and the ability to promote wound healing.

[0076] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects. The scope of the invention is defined by the appended claims rather than the foregoing description, and thus all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0077] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a biodegradable polymer hemostatic sponge, characterized in that, Includes the following steps: S1. Prepare adipic acid dihydrazide-terminated polyurethane emulsion and oxidized hyaluronic acid, respectively; S2. Dissolve oxidized hyaluronic acid in deionized water, remove dissolved oxygen from the deionized water with nitrogen, add dopamine hydrochloride, react in the dark under a nitrogen atmosphere for 12 hours, dialyze the reaction solution in deionized water for three days, and finally freeze-dry to obtain dopamine-modified oxidized hyaluronic acid with antioxidant function, scavenging reactive oxygen species and promoting wound repair after introducing catechol groups. S3. A polyurethane emulsion with adipic acid dihydrazide end-capped is used as component A; Oxidized hyaluronic acid solution and dopamine-modified oxidized hyaluronic acid solution were prepared together as component B and mixed in different proportions to form a precursor solution. Liquid nitrogen was added to the precursor solution in small amounts multiple times under high-speed mechanical stirring. After sufficient cooling and mixing, the solution was loaded into a mold, and after being frozen overnight at sub-zero temperatures, it was freeze-dried to obtain polyurethane-dopamine-modified oxidized hyaluronic acid sponge. The specific preparation method of the polyurethane emulsion with adipate dihydrazide end-capped in S1 is as follows: the macromolecular diol is dehydrated at 90-100℃ for 2 hours, then aliphatic diisocyanate and organic bismuth are added, and the mixture is prepolymerized at 78℃ for 2 hours. After adding 2,2-dimethylolpropionic acid, the chain extension reaction is carried out at 75℃ for 1 hour. After cooling, an appropriate amount of acetone is added to dissolve the polyurethane prepolymer. Triethylamine is added and reacted for 30 min. An appropriate amount of adipate dihydrazide is dissolved in deionized water and emulsified with the above polyurethane solution by high-speed stirring for 1 hour. After dialyzing in deionized water for three days with a dialysis bag with a molecular weight cutoff of 3500, the solid content of the emulsion is adjusted to finally obtain the polyurethane emulsion with adipate dihydrazide end-capped. The macromolecular diol includes one or more of polycaprolactone, polyethylene glycol, polytetramethylene glycol, and polylactic-co-glycolic acid copolymer; the polycaprolactone has a weight-average molecular weight of 600-2000; the polyethylene glycol has a weight-average molecular weight of 400-2000; and the polytetramethylene glycol has a weight-average molecular weight of 800. 2000; Polylactic acid The weight-average molecular weight of the glycolic acid copolymer is 1000. 3000; Aliphatic diisocyanates include L Lysine diisocyanate, hexamethylene diisocyanate, 4,4' At least one of dicyclohexylmethane diisocyanate and isophorone diisocyanate; The molar ratio of the aliphatic diisocyanate to the macromolecular diol is 2.0:1 to 3.0:

1.

2. The method for providing a biodegradable polymer hemostatic sponge according to claim 1, characterized in that, The molar ratio of the aliphatic diisocyanate to the macromolecular diol is 2.7:

1.

3. The method for providing a biodegradable polymer hemostatic sponge according to claim 1, characterized in that, The specific preparation method of oxidized hyaluronic acid in S1 is as follows: weigh hyaluronic acid and add it to deionized water, stir to dissolve it completely; add the sodium periodate solution that has been dissolved in deionized water to the hyaluronic acid solution, react at 25°C in the dark for 8 hours, finally add an appropriate amount of ethylene glycol to terminate the reaction, then dialyze the reaction solution for three days and freeze dry to obtain oxidized hyaluronic acid.

4. The method for providing a biodegradable polymer hemostatic sponge according to claim 1, characterized in that, In S3, component A is an amino-terminated polyurethane emulsion with a mass fraction of 10-30%. Component B is an aqueous solution of catechol-modified oxidized hyaluronic acid with a mass fraction of 2-5%, wherein the ratio of component A to component B is 1:2 to 2:1; and the ratio of oxidized hyaluronic acid to dopamine-modified oxidized hyaluronic acid is 3:1 to 1:

1. The polyurethane-dopamine modified oxidized hyaluronic acid sponge needs to be left to stand for more than 5 minutes to gel.

5. The method for providing a biodegradable polymer hemostatic sponge according to claim 4, characterized in that, The ratio of component A to component B is 1.5:1; the ratio of oxidized hyaluronic acid to dopamine-modified oxidized hyaluronic acid is 3:1; and the polyurethane-dopamine-modified oxidized hyaluronic acid sponge is allowed to stand for 5 to 15 minutes to form a gel.

6. The biodegradable polymer hemostatic sponge prepared by any one of claims 1 to 5.

7. The application of the biodegradable polymer hemostatic sponge according to claim 6 in the preparation of biological hemostatic materials.

Citation Information

Patent Citations

  • Preparation method of biodegradable medical polyurethane and chitosan composite hemostatic sponge

    CN105944138A

  • Polyurethane elastomer hemostatic sponge capable of rapidly stopping bleeding and preparation method of polyurethane elastomer hemostatic sponge

    CN116077713A

  • Nasal cavity hemostatic cotton with gradient distribution of cell apertures

    CN214209030U

  • Antibacterial hemostatic non-woven cotton and preparation method thereof

    CN112472864A

  • Degradable intravascular stent with sustained-release drug coating and preparation method of degradable intravascular stent

    CN114246992A